Sulforaphane regulates cell proliferation and induces apoptotic cell death mediated by ROS-cell cycle arrest in pancreatic cancer cells - Cho, Yongmin; Park, Moon Nyeo; Choi, Min; Upadhyay, Tarun Kumar; Kang, Han Na; Oh, Jeong Min; Min, Soonki; Yang, Ji-Ung; Kong, Moonkyoo; Ko, Seong-Gyu; Rahman, Md Ataur; Harrath, Abdel Halim; et al. (Frontiers in Oncology, 2024)
BackgroundPancreatic cancer (PC), sometimes referred to as pancreatic ductal adenocarcinoma (PDAC), is a major cause of global mortality from cancer. Pancreatic cancer is a very aggressive and devastating kind of cancer, characterized by limited options for therapy and low possibilities of survival. Sulforaphane (SFN), a naturally occurring sulfur-containing compound, is believed to possess anti-inflammatory, anti-obesity, and anti-cancer characteristics.ObjectiveHowever, efficient preventative and treatment measures are essential and SFN has been studied for its ability to suppress pancreatic cancer cell proliferation and induce apoptosis.MethodsHere, SFN induced cytotoxicity and apoptosis in PDAC cell lines such as MIA PaCa-2 and PANC-1 cells, as evaluated by cytotoxicity, colony formation, western blot analysis, fluorescence-activated cell sorting (FACS), reactive oxygen species (ROS) detection, caspase-3 activity assay, immunofluorescence assay, and mitochondrial membrane potential assay.ResultsIn MIA PaCa-2 and PANC-1 cells, SFN inhibited cell survival and proliferation in a dose-dependent manner. The activation of caspase zymogens results in cleaved PARP and cleaved caspase-3, which is associated with an accumulation in the sub G1 phase. Furthermore, SFN increased ROS level and γH2A.X expression while decreasing mitochondrial membrane potential (ΔΨm). Notably, the ROS scavenger N-Acetyl-L-cysteine (NAC) was shown to reverse SFN-induced cytotoxicity and ROS level. Subsequently, SFN-induced cell cycle arrest and apoptosis induction as a Trojan horse to eliminate pancreatic cancer cells via ROS-mediated pathways were used to inhibit pancreatic cancer cells.ConclusionCollectively, our data demonstrates that SFN-induced cell death follows the apoptosis pathway, making it a viable target for therapeutic interventions against pancreatic cancer.